Pengembangan Bahan Ajar Materi Gelombang Berjalan Dan Stasioner Kelas XI SMA Berbasis Video Animasi Whiteboard - Melania Assumpta Puang; Oktavianus Ama Ki`i; Claudia Mariska M. Maing (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
This study aims to 1) determine the feasibility of physics teaching materials based in the whiteboard animation video that was developed, 2) find out the reponses of teacher and students based on the developed whiteboard animation video, 3) find out the learning outcomes of students on whiteboard animation videos in moving waves and stasionary waves class XI SMA developed. The type of research used in Research and Development using the ADDIE development stage (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques use tests and questionnaires to obtain the feasibility of teaching materials media and studen learning outcomes in the test stage field trial. The results showed 1) the validation assessment of the material expert was 75,7% in the very good category and was in the average score of 3,035 in the very good category, 2) the validity assessment from media experts was 75% in the good and mean score 3 in the very good category, 3) the teacher’s response is 83,3% in the very good category and having an average score of 3,33 in the very good category,4) the learning outcomes obtained by students are on average 82 meeting the KKM.